TINJAUAN HUKUM PELAKSANAAN EKSEKUSI RIIL DALAM PUTUSAN PERADILAN PERDATA - Muhammad Fadhilah (Universitas 17 Agustus 1945 Samarinda, 2020)
Abstract Execution is an obligation that must be carried out by the court based on a legal basis in accordance with Article 54 paragraph (2) of Law Number 48 of 2009 concerning Judicial Power which expressly stipulates that the implementation of court decisions in civil cases is carried out by the Registrar and the bailiff led by the Chairman. Court.It is necessary to increase socialization regarding the rules and or procedures for execution to the public so that the public can better understand that the theory of legal certainty is able to protect the interests and rights of the community, as well as increase compliance with the rule of law and respect for the rights of fellow citizens.For officials in the judiciary, it is necessary to increase understanding that the law must be enforced as well as possible in a balanced manner in protecting the interests of the parties so that the implementation of court decisions or executions must be maximized so that all justice-seeking efforts do not only win on paper but can be realized. in fact. Keywords: Execution. Court Decision